2015
DOI: 10.1371/journal.pone.0126575
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Attitude towards Breastfeeding among Two Generations of Indian Women: A Comparative Study

Abstract: IntroductionPresent study was aimed to analyze the impact of education, employment and financial independence in breastfeeding practices among Indian women.MethodologyPresent explorative questionnaire based survey included 256 women (128 pairs) in the final analysis. A pair means – a) pregnant lady (in her third trimester) representing younger generation and b) her mother/mother in law representing the elder generation.ResultsWe found that the overall awareness regarding ‘breast milk’ being the best food for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 4 publications
4
18
0
Order By: Relevance
“…Colostrum on other hand has got immunologic benefit for the newborn and therefore should be fed to the baby. Our study shows according 68.9% respondent colostrum should be fed to the new born baby, which is similar to the study done by Chinnasami et al 19 where 75% had correct knowledge about colostrum and also study done by Pandey et al 17 showed 78.1% mothers of younger generation agreed that colostrum to be fed to the baby. The lower values on regards to colostrum intake is due to prevalent traditional cultural customs and negative perception on colostrum feeding, as first milk is very dirty and so must be discarded.…”
Section: Discussionsupporting
confidence: 89%
“…Colostrum on other hand has got immunologic benefit for the newborn and therefore should be fed to the baby. Our study shows according 68.9% respondent colostrum should be fed to the new born baby, which is similar to the study done by Chinnasami et al 19 where 75% had correct knowledge about colostrum and also study done by Pandey et al 17 showed 78.1% mothers of younger generation agreed that colostrum to be fed to the baby. The lower values on regards to colostrum intake is due to prevalent traditional cultural customs and negative perception on colostrum feeding, as first milk is very dirty and so must be discarded.…”
Section: Discussionsupporting
confidence: 89%
“…7 In the present study, 46% mothers had awareness about importance of colostrum believed that colostrum was good to feed, and 95.6% mothers actually fed it immediately to their babies which was a good and close observation to the Manipal University study by Pandey et al where 75% mothers fed colostrum to their babies and about 90% had awareness. 2 Only 51.2 % of our mothers were aware of the advantages of breastfeeding. Significant difference was found in number of women with knowledge about breast feeding with respect to parity.…”
Section: Discussionmentioning
confidence: 90%
“…2 More than 15% of 24 lakhs child deaths could be avoided in India by optimal breastfeeding practices, but very few women in India have access to counselling services on infant and young feeding. Despite the knowledge of benefits of breastfeeding, its prevalence and duration among general population in many countries are still lower than the international recommendations of 6 months of exclusive breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…3 Studies have shown that although moderately high initiation rates of breastfeeding exist in India, the prevalence and duration of exclusive breast feeding is very low, due to various factors that are difficult to address through breastfeeding promotion interventions. [4][5][6] Several authors [7][8][9] assert that a focus on modifiable factors such as maternal, paternal and significant others infant feeding attitude may help to increase breastfeeding duration. In cosmopolitan city where women are geographically isolated from their own mothers or other family members, the support of fathers as breastfeeding advocates may be more influential.…”
Section: Introductionmentioning
confidence: 99%